Caracterización de Las Principales Manifestaciones Bucodentales en Niños Con VIH Positivo Pertenecientes a Una Fundacion de la Ciudad de Neiva - Rodríguez Castillo, Francisco; Cuenca Cuadros, Marlio Andrés; Charry García, Angie Melissa (Universidad Antonio Nariño, 2021)
Oral lesions in patients with HIV is one of the first signs of this viral disease about deterioration of the immune system, these lessons can complicate the stability of the patient and therefore it is important to collect as much information is possible in order to establish not only its prevalence, but also the oral management that must be carried out. Objective: Characterization of the oral main manifestations in HIV positive children in one foundation from Neiva City. Materials and Methods: Corresponds to descriptive research, with a correlational depth and cross section, which aims to solve the questions about the relationship between oral lesions and the development of dentition in children diagnosed with HIV positive, using a data collection instrument (Survey) which will be applied to a sample of 45 children in a foundation from Neiva. Results: The characteristics of the analyzed lesions include the type, size and shape: according to this it was identified that 57% of the population had red lesions smaller than 1 cm; 50% had white lesions less than 1 cm; 50% of red lesions are flattened and with respect to white lesions 86% also have a flattened shape. Conclusions: Is no relationship between age and the presence of oral lesions according to descriptive statistical analysis.